Pintura Moderna Soviética. - Carreiro, Carlos; Chaves, Joaquim Matos (Porto : Rosart Amorim - Galeria da Praça, 1990)
Nikolaevich, Akimov Ivan ; Tadjanovich, Amalbashian Sarkis ; Vladimir, Beriozkin ; Petrovich, Fedosov Nikita ; Mikhail, Gadjikaéssimov ; Iuris, Iurians ; Franceska, Kirke ; Anatolij, Kulinich ; Datse, Liela ; Georgi, Litichevski ; Viktorovits, Medvedev Andrei ; Vassilievich, Mironov Boris ; Pavlovich, Ossovski Peter ; Petrovich, Ossovski Sergei ; Amaiakovich, Ovsepian Gamlet ; Miervaldis, Polis ; Leonid, Purygin ; Lauma, Sica ; Lavrentievich, Sidorov Fiodor ; Dmitriyevich, Sokolov Alexei ; Edward, Steinberg ; Leonid, Stupenkov ; Petrovich, Sveshnikov Boris ; Maia-Nora, Tabaca ; Gabrielovich, Terzian Karapet ; Djavlon, Umarbekov ; Edgars, Verpe ; Via, Zarinha
biografie
Engels & Portugees
boek
Keywords: Rusland